Efficacy of Retinoids in IKZF1-Mutated BCR-ABL1 Acute Lymphoblastic Leukemia - Churchman, Michelle L; Low, Jonathan; Qu, Chunxu; Paietta, Elisabeth M; Kasper, Lawryn H; Chang, Yunchao; Payne-Turner, Debbie; Althoff, Mark J; Song, Guangchun; Chen, Shann-Ching; Ma, Jing; Rusch, Michael; et al. (Cancer cell, 2015)
Alterations of IKZF1, encoding the lymphoid transcription factor IKAROS, are a hallmark of high-risk acute lymphoblastic leukemia (ALL), however the role of IKZF1 alterations in ALL pathogenesis is poorly understood. Here, we show that in mouse models of BCR-ABL1 leukemia, Ikzf1 and Arf alterations synergistically promote the development of an aggressive lymphoid leukemia. Ikzf1 alterations result in acquisition of stem cell-like features, including self-renewal and increased bone marrow stromal adhesion. Retinoid receptor agonists reversed this phenotype, partly by inducing expression of IKZF1, resulting in abrogation of adhesion and self-renewal, cell cycle arrest, and attenuation of proliferation without direct cytotoxicity. Retinoids potentiated the activity of dasatinib in mouse and human BCR-ABL1 ALL, providing an additional therapeutic option in IKZF1-mutated ALL.